1998
DOI: 10.1038/sj.bmt.1701064
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-leukemia effects in T lineage and B lineage acute lymphoblastic leukemia

Abstract: Summary:Allogeneic bone marrow transplantation is an effective treatment for acute lymphoblastic leukemia (ALL). 1 This efficacy is, in part, mediated by graft-versus-leukemia T and B lineage ALL cells express different levels of HLA-class II antigens, which may serve as targets for effects (GVL). 2,3 GVL is greatest in patients with acute or chronic graft-versus-host disease (GVHD). T cells are graft-versus-host disease (GVHD) and graft-versus-leukemia (GVL). The object of this study was to determine importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 2 publications
4
54
0
Order By: Relevance
“…15 Furthermore, the high OS rate of patients transplanted with active disease and no reinduction attempt may be due to the high incidence of extensive cGHVD in this subgroup (75 vs 39% in the reinduction group), which possibly correlates with a more potent GVL effect. 38,39 Whether this increased incidence of cGHVD has a biological explanation or whether it is due to statistical effects is difficult to say as we have not found a difference in conditioning regimen, donor type, stem cell source or use of prophylactic DLIs between the two groups. Kaplan-Meyer survival analysis suggested that the development of cGVHD leads to significantly better OS.…”
Section: Discussionmentioning
confidence: 58%
“…15 Furthermore, the high OS rate of patients transplanted with active disease and no reinduction attempt may be due to the high incidence of extensive cGHVD in this subgroup (75 vs 39% in the reinduction group), which possibly correlates with a more potent GVL effect. 38,39 Whether this increased incidence of cGHVD has a biological explanation or whether it is due to statistical effects is difficult to say as we have not found a difference in conditioning regimen, donor type, stem cell source or use of prophylactic DLIs between the two groups. Kaplan-Meyer survival analysis suggested that the development of cGVHD leads to significantly better OS.…”
Section: Discussionmentioning
confidence: 58%
“…In 2 out of 16 patients, the leukemia relapsed very rapidly within 12 weeks although post-SCT MRD levels in blood and bone marrow became negative (that is, o1 Â 10 À4 ) immediately after SCT. In 8 out of the 14 remaining patients, a bone marrow and/or a blood sample with a high MRD level (X1 Â 10 À4 ) preceded the clinical relapse by 9 weeks (median, range 0-30) and 8 weeks (median, range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], respectively. The slightly earlier detection in bone marrow occurred despite more frequent sampling of blood than of bone marrow.…”
Section: Mrd Monitoring After Transplantation Predicts Relapsementioning
confidence: 99%
“…[10][11][12][13] The occurrence of graft versus host disease (GvHD) and reduction of immunosuppressive medication shortly after SCT has been reported to correlate with protection against relapse of ALL albeit less strongly than for other, especially myeloid type, hematological malignancies. 10,[14][15][16] The administration of donor lymphocyte infusion (DLI) at the time of overt relapsing ALL was usually not effective.…”
Section: Introductionmentioning
confidence: 99%
“…6 There is evidence for a GVL effect in ALL; GVHD is associated with lower RI and allo-SCT provides significant benefit over autologous transplant. 3,7,8 A reduced intensity conditioning (RIC) approach may reduce RI and lower TRM, extending applicability to older patients and those with comorbidities. Several retrospective studies have examined RIC allo-SCT for ALL.…”
Section: Introductionmentioning
confidence: 99%